2015
DOI: 10.1371/journal.pone.0143801
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Palladium Nanoparticles Affects Serum Levels of Cytokines in Female Wistar Rats

Abstract: BackgroundInformation currently available on the impact of palladium on the immune system mainly derives from studies assessing the biological effects of palladium salts. However, in the last years, there has been a notable increase in occupational and environmental levels of fine and ultrafine palladium particles released from automobile catalytic converters, which may play a role in palladium sensitization. In this context, the evaluation of the possible effects exerted by palladium nanoparticles (Pd-NPs) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“…The data show remarkable increases in different cytokines, in the 2 nd and 3 rd groups. This result may be in harmony with those of Iavicoli et al, who concluded that administration of nanoparticle induced a significant increase of different cytokines as IL-1α, IL-4, IL-6, IL-10, IL-12, GM-CSF and INF-γ [20]. Not only quantitative measurement of these cytokines, but also Khan et al, reported a transient increase in IL-1β, IL-6 and TNF-α gene expressions in rat livers exposed to gold nanoparticles by using qRT-PCR and different primer sequences used for real-time PCR amplifications for different pro-inflammatory cytokines [29,30].…”
Section: Gheithsupporting
confidence: 91%
See 1 more Smart Citation
“…The data show remarkable increases in different cytokines, in the 2 nd and 3 rd groups. This result may be in harmony with those of Iavicoli et al, who concluded that administration of nanoparticle induced a significant increase of different cytokines as IL-1α, IL-4, IL-6, IL-10, IL-12, GM-CSF and INF-γ [20]. Not only quantitative measurement of these cytokines, but also Khan et al, reported a transient increase in IL-1β, IL-6 and TNF-α gene expressions in rat livers exposed to gold nanoparticles by using qRT-PCR and different primer sequences used for real-time PCR amplifications for different pro-inflammatory cytokines [29,30].…”
Section: Gheithsupporting
confidence: 91%
“…Serum ferritin and C-reactive protein levels were determined by ELISA method. And a multiplex biometric ELISA was adopted for determination of IL-1α, IL-6, and TNF-α according to methods cited in Iavicoli1 et al [20].…”
Section: Laboratory Analysis Of Different Parametersmentioning
confidence: 99%
“…In fact, ROS can attack biomolecules and induce genotoxic damage, cell dysfunction, and cell death [ 27 ]. Iavicoli et al [ 28 ] have reported that PdNPs caused a significant increase in DNA fragmentation in female Wistar rats. Hu et al [ 29 ] have reported that cell toxicity induced by ROS accompanies an increase in lipid peroxides.…”
Section: Discussionmentioning
confidence: 99%
“…Several biological models, from bacterial strains [ 51 ] to mammalian organisms were reported to be affected by Pd-NP treatment. The immune [ 52 , 53 ], renal [ 54 ] and endocrine systems [ 55 ] were demonstrated as critical targets for the toxic action of Pd-NPs ( Table 2 ). The elemental Pd content in urine, and changes in cytokine serum levels, urinary protein content and hormonal serum concentrations, emerged as possible biomarkers of Pd-NP exposure and early effect, although further studies are necessary to confirm these preliminary results and validate their possible employment in real exposure settings.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Concerning in vivo results, investigations conducted on female Wistar rats, proved the ability of Pd-NPs to significantly affect the immune system of treated animals inducing alterations in the serum levels of several cytokines secreted by different T helper (Th) lymphocyte subsets [ 52 , 53 ]. A subacute (14 days) exposure to increasing doses of Pd-NPs was able to induce a general, although not significant, upward trend, in all cytokine serum concentrations investigated, while a significant increase was only determined by the highest dose of Pd-NPs (12 μg/kg) [ 52 ]. These findings may suggest that Pd-NPs could exert a significant and generalized stimulatory impact on the immune system of exposed rats.…”
Section: In Vivo Studiesmentioning
confidence: 99%